Getting under the skin : the body and media theory - Wegenstein, Bernadette (MIT Press, 2006)
"The body as an object of critical study dominates disciplines across the humanities to such an extent that a new discipline has emerged: body criticism. In Getting Under the Skin, Bernadette Wegenstein traces contemporary body discourse in philosophy and cultural studies to its roots in twentieth-century thought - showing how psychoanalysis, phenomenology, cognitive science, and feminist theory contributed to a new body concept - and studies the millenial body in performance art, popular culture, new media arts, and architecture."--Jacket